HUBUNGAN PARTISIPASI MATA KULIAH OLAHRAGA PERMAINAN TRADISISONAL TERHADAP KESEJAHTERAN MENTAL MAHASISWA PGSD UNM - Isrika; Wilda; Nurilmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between participation in the Traditional Sports Games course and the mental well-being of students in the Primary Teacher Education Program (PGSD) at Universitas Negeri Makassar (UNM). The study used a quantitative approach with an explanatory correlational design involving 206 PGSD UNM students who were taking or had completed the Traditional Sports Games course. The research instruments used the WHO-5 Well-Being Index to measure mental well-being and a participation questionnaire based on a lecture enthusiasm scale. Data analysis used Pearson correlation and simple linear regression at a significance level of 0.05. Results showed that the majority of students (55.3%) were in the 'sometimes' category of lecture enthusiasm, while 27.7% were in the 'rarely' category. There is a positive and significant relationship between the intensity of participation in traditional sports games courses and students' mental well-being. Traditional games that are collaborative, enjoyable, and contain local cultural values have proven to be effective as a promotive strategy for mental health in the university environment.